EXPERIMENTAL RESEARCH OF MAGNETOPHORESIS AND BROWNIAN DIFFUSION INFLUENCE ON “MAGNETIC WEIGHT” OF MAGNETIC LIQUID - V. G. Bashtovoi; F. G. Reks; S. V. Klimovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper investigates an influence of diffusion processes of Brown magnetic particles in  magnetic liquid on the forces that operate in the volume of  liquid  being in an external non-uniform magnetic  field.  It has been shown that due to processes of mass transfer  leading to redistribution of particles’ concentration static distribution of pressure in the liquid can undergo considerable changes in the course of time and change conditions of its balance.